Der ontologische Gottesbeweis - Hermanni, Friedrich (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2000)
The essay discusses three versions of the ontological proof, i.e. first the version advocated by Anselm and Descartes, second the version that assumes the notion of God as an absolute ens necessarium, and a third version developed by the author following Leibniz’ theory of the striving possibles. In addition, the three most important objections against the ontological proof are discussed, namely the so-called logical objection, the objection disputing the conceivableness of God, and finally the objection raised by Kant. Evidence is being given that the logical objection is definitely wrong and that through the two other objections the first and the second version are vitiated, whereas the third is not disproved. The thesis is that the third version presents, in fact, a valid proof of God’s existence.